Antagonist targeting microRNA-155 protects against lithium-pilocarpine-induced status epilepticus in C57BL/6 mice by activating brain-derived neurotrophic factor - Zhengxu eCai; song eli; sheng eli; Fan eSong; Zhen eZhang; Guanhua eQi; Tianbai eLi; Juanjuan eQiu; Jiajia eWan; Hua eSui; Hua eSui; Huishu eGuo (Frontiers Media S.A., 2016)
Epilepsy is a severe brain disorder affecting numerous patients. Recently, it is inferred that modulation of microRNA-155 (miR-155) could serve as a promising treatment of mesial temporal lobe epilepsy (MTLE). In the current study, the therapeutic potential of miR-155 antagonist against TLE was evaluated and the underlying mechanism involved in this regulation was explored. TLE model was induced by lithium-pilocarpine method. The effect of miR-155 antagonist on epilepticus symptoms of TLE mice was assessed using Racine classification and electroencephalogram (EEG) recordings. The expression of brain-derived neurotrophic factor (BDNF) and its association with miR-155 were also assessed with a series of experiments. Our results showed that level of miR-155 was significantly up-regulated after induction of TLE model. Based on the results of EEG and behavior analyses, seizures in mice were alleviated by miR-155 antagonist. Moreover, administration of miR-155 antagonist also significantly increased the level of BDNF. The results of dual luciferase assay and western blotting showed that miR-155 antagonist exerted its action on status epilepticus by directly regulating the activity of BDNF. Taken all the information together, our results demonstrated that miR-155 antagonist might firstly induce the expression of BDNF, which then contributed to the alleviation of epilepsy in the current study.